Positive thinking training for improving self-acceptance of children in correctional facility - Putri Nabila Bilicha; Fuad Nashori; Indahria Sulistyarini (University of Muhammadiyah Malang, 2022)
Conflicting with the law will make them feel a lot of pressure and psychological changes like shame, regret, and unable to accept themselves. If they have positive thinking, they will easily accept their condition. This study aimed to observe the effect of positive thinking training in improving the self-acceptance of juveniles who were undergoing a period of correctional program. The subjects of this study included 24 juveniles at Class I Juvenile Correctional Facility Kutoarjo, all male aged 14-17 years with a minimum educational level of primary school, a minimum of 1-month correctional program, and first-time criminal sentence. Self-acceptance was measured using the RISA self-acceptance scale (2014). The research method used was an experimental method with the pretest posttest with control group design. The results of this study indicated that self-acceptance score of the subjects in the experimental group has increased after they received positive thinking training. It can be seen from the increase of the mean score from 33.58 with SD = 3,919 in the pre-test to 41.42 with SD = 6,259 in the post-test. It’s means that positive thinking training can effectively increase self-acceptance of children in LPKA Class I Kutoarjo.